Moral Culture of Personality in the Creative Legacy of Ivan Ohienko - Hryhoriy Vasianovych (Pedagogical Discourse, 2012)
The article analyses the essence, the contents and components of moral culture in the context of Ivan Ohienko’s artistic legacy. On the basis of original sources the author proves that outstanding teacher, educational and religious figure Ivan Ohienko – Metropolitan Ilarion grounded moral culture of the personality in the indissoluble connection with his/her consciousness, activity and moral relations.